(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
The purpose of this work is to investigate the batch removal of Pb2+ from aqueous solutions using marine dried brown seaweed S. baccularia. Seaweed was used as a low-cost adsorbent. The effects of pH, contact time, temperature, shaking speed and the concentration of the Pb2+ solution were examined in the biosorption process with S. baccularia. The results showed that when S. baccularia was used as the bioadsorbent, the optimum pH, Pb2+ concentration, equilibrium time, temperature, and shaking speed were 3, 20 ppm, 120 min, 30°C, and 120rpm. The equilibrium adsorption data are fitted to the Langmuir isotherm model. The separation factor (RL) in the experiment was less than one (<1), indicating that the adsorption of metal ions on Sargassum baccularia adsorbent is favorable. The calculated activation energy (Ea) implies that the adsorption of Pb (II) on brown seaweed is a physical adsorption. Thermodynamic results show that adsorption occurs spontaneously in nature